Pancreaticoduodenectomy and portal-superior mesenteric vein reconstruction using autologous grafts in patients with periampullary cancer: Preliminary experience at Bach Mai Hospital - Duong Duc Hung; Nguyen Thanh Khiem; Nguyen Ham Hoi; Luong Tuan Hiep (Vietnam Journal of Science, Technology and Engineering)
Portal vein/superior mesenteric vein (PV/SMV) resection and reconstruction during pancreaticoduodenectomy (PD) represent one of the most complex procedures in digestive system surgery. Each technique for portal vein reconstruction has distinct advantages and disadvantages, making the optimal approach a subject of ongoing debate. From October 2020 to October 2024, patients with periampullary cancer who underwent PD with PV/SMV resection and reconstruction using autologous grafts were documented. The data collected included basic information, clinical characteristics, surgical details, and post-operative graft conditions. Results indicated that during the study period, eight cases of vein reconstruction using autologous grafts (falciform ligament/segment or an alternative vein) were performed. No cases of early or late graft thrombosis or stenosis were reported. In conclusion, PV/SMV reconstruction using autologous grafts in PD is feasible and enhances the potential for achieving radical surgery in cases of locally invasive duodenalpancreatic head cancer.